Consequence of extreme warm environment on hepatic and serum vitamin A and enzymes in Marwari goats - SHARMA, A K; PURI, G (The Indian Journal of Animal Sciences, 2013)
A study was conducted to investigate liver and serum carotene, vitamin A and enzymes i.e. aspartate amino transferase(AST) and alanine amino transferase (ALT) during winter and summer in 300 Marwari goats. In each climatic condition 150 animals were taken. They were categorized into males (70 of 0–1 year, and 30 of above 1 year) and females (30 of 0–1 year, and 20 of above 1 year). Liver carotene (μg/g), vitamin A (μg/g), AST (IU/L) and ALT (IU/L) ranged from 3.25 to 11.36, 156.56 to 290.25, 210.56 to 610.10 and from 170.11 to 562.70, respectively. Serum carotene (μg/dl), vitamin A (μg/dl), AST (IU/L) and ALT (IU/L) ranged from 36.24 to 78.65, 22.45 to 62.55, 56.70 to 215.00 and from 20.15 to 85.77 (average 57.54±1.24), respectively. Season had significant effect on liver and serum carotene, vitamin A and ALT. Liver carotene, vitamin A and ALT showed significant effect on sex in both climatic conditions and age group in winter. Higher values were observed in all the liver parameters in males than females in both climatic conditions. Higher values of all liver parameters were observed in 0–1 year age group animals than above 1 year age group in both climatic conditions except in summer values of ALT were was higher in above 1 year age group animals. Serum AST showed significant effect of sex in both climatic conditions while, serum vitamin A and ALT showed significant effect on age group in summer only. Higher values of serum carotene and AST were observed in male while serum vitamin A and ALT values were higher in female of both climatic conditions.